2015
DOI: 10.1007/s10695-015-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase 2-like and Na+-K+-ATPase α gene expression in medaka (Oryzias latipes) under carbonate alkalinity stress

Abstract: High carbonate alkalinity is one of the major stress factors for living organisms in saline-alkaline water areas. Acute and chronic effects of carbonate alkalinity on expression of two genes, carbonic anhydrase 2-like (CA2-like) and Na(+)-K(+)-ATPase α subunit (NKA-α) mRNA in medaka (Oryzias latipes) were evaluated to better understand the responses important for coping with a carbonate alkalinity stress. In the acute exposure experiment, the expression of CA2-like and NKA-α mRNA in the gill and kidney of meda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The area of saline–alkaline land in Northeast China is approximately 3.78 × 10 6 hm2, and most is carbonate saline–alkaline land ( 3 , 4 ). The saline–alkaline water in the region has characteristics such as low salinity, high alkalinity, and high pH, resulting in low bioavailability ( 5 ). The development of fisheries in regions of saline‒alkaline water is important in the utilization of abundant environmental resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of saline–alkaline land in Northeast China is approximately 3.78 × 10 6 hm2, and most is carbonate saline–alkaline land ( 3 , 4 ). The saline–alkaline water in the region has characteristics such as low salinity, high alkalinity, and high pH, resulting in low bioavailability ( 5 ). The development of fisheries in regions of saline‒alkaline water is important in the utilization of abundant environmental resources.…”
Section: Introductionmentioning
confidence: 99%
“…The development of fisheries in regions of saline‒alkaline water is important in the utilization of abundant environmental resources. The high alkalinity of saline–alkaline water is highly detrimental to fish, threatening their growth and health and limiting the development of the aquaculture industry ( 5 7 ). The water in Qinghai Lake has high alkalinity (carbonate alkalinity of approximately 29 mM, pH 9.1-9.5) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…CA is considered a crucial stress factor as it affects the survival of aquatic animals in saline-alkali water [ 6 ]. Previous studies have shown that carbonate alkalinity could cause a series of problems for aquatic animals, such as respiratory and metabolic alkalosis [ 7 ], tissue oxidative damage [ 8 ], intestinal flora imbalance [ 9 ], as well as disorders of the antioxidant and immune system [ 10 ], which seriously affect the normal growth, development and reproduction of fish. At the same time, recent studies have shown that the extent of freshwater salinization continues to deepen as a result of human activities and global warming, which might steadily shrink the available space for freshwater aquaculture [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alkalinity stress is considered the main stress in salinealkali water habitats and can suppress the growth, reproduction, development, survival, and even intestinal microflora of aquatic animals [8,9]. Alkalinity stress increases the blood HCO 3 − concentration and disrupts the balance of NH 3 and NH 4 + due to a lack of H + , which finally results in ammonia poisoning [10].…”
Section: Introductionmentioning
confidence: 99%